Meningkatkan Daya Saing UMKM Melalui Sertifikasi Halal - Fadhli, Khotim; Fahimah, Mar’atul; Rahmawati, Ita; Bisari, Nia Aprilia; Juma’izah, Rizatul; Saputri, Maya Kurnia; Qodri, Hanif Fauzan; Ramadhani, M. Hanif; Koiriyah, Safinatul (Jumat Ekonomi: Jurnal Pengabdian Masyarakat, 2024)
Micro, Small and Medium Enterprises (MSMEs) are a vital sector in the Indonesian economy, but face challenges in competitiveness in the era of globalization. The lack of understanding by MSME actors regarding halal certification and marketing strategies is an obstacle in the development of their businesses. Halal certification not only increases Muslim consumer confidence but also opens up global market opportunities, while effective marketing strategies can expand market reach. KH University Community Service Team. A. Wahab Hasbullah (Unwaha) implemented an empowerment program in Ngusikan District, East Java, to overcome this problem. This program includes outreach on the importance of halal certification and marketing training, including digital marketing, marketplace management, branding and sales strategies. The Participatory Action Research (PAR) method is used to involve MSME actors in the process of problem identification, solution and implementation. Continuous assistance is also carried out through monitoring, evaluation and guidance with the Unwaha Halal Center. As a result, coached MSMEs show increased consumer confidence, wider market reach, and income growth. This program not only provides short-term solutions but also builds the capacity of MSMEs to compete in the domestic market, supporting inclusive and sustainable economic growth. Halal certification and effective marketing strategies have proven to be an important foundation for supporting the sustainability of MSMEs in a market that is currently facing global competition.